Relationship between mandibular symphysis dimensions and mandibular anterior alveolar bone thickness as assessed with cone-beam computed tomography - Foosiri,Pimchanok (2018)
ABSTRACT Objective: To determine the relationship between symphysis dimensions and alveolar bone thickness (ABT) of the mandibular anterior teeth. Methods: Cone-beam computed tomography images of 51 patients were collected and measured. The buccal and lingual ABT of the mandibular anterior teeth was measured at 3 and 6 mm apical to the cemento-enamel junction (CEJ) and at the root apices. The symphysis height and width were measured. The symphysis ratio was the ratio of symphysis height to symphysis width. Kendall’s tau correlation coefficient was used to determine the relationships between the variables at a 0.05 significance level. Results: The mandibular anterior teeth lingual and apical ABT positively correlated with symphysis width (p<0.05). Moreover, these thicknesses negatively correlated with the symphysis ratio (p<0.05). Symphysis widths and ratios showed higher correlation coefficients with total and buccal apical ABT, compared with lingual ABT. Buccal ABT at 3 and 6 mm apical to the CEJ was not significantly correlated with most symphysis dimensions. The mean thickness of the buccal alveolar bone at the upper root half was only 0.2-0.6 mm, which was very thin, when compared with other regions. Conclusion: For mandibular anterior teeth, the apical alveolar bone and lingual alveolar bone tended to be thicker in patients with a wide and short symphysis, compared to those with a narrow and long symphysis. Buccal alveolar bone was, in general, very thin and did not show a significant relationship with most symphysis dimensions.